Analisis Faktor Yang Mempengaruhi Minat Berkunjung Ulang Pasien Rawat Jalan Di Rumah Sakit Islam Sultan Agung Banjarbaru - anggi nooropie maharani; Rahman, Andri Nur; Hastuti, Eny (STIKES Garuda Putih, 2025)
The interest in repeat visits is an illustration of a hospital's success in creating a quality hospital in terms of its services. Patients returning to the same health service means that the reality they receive is higher than what they expected, resulting in patient loyalty to the hospital. This research aims to find out what factors influence the interest in revisiting outpatients at RSI Sultan Agung Banjarbaru. This research uses a cross-sectional approach with causal quantitative methods. The population and sample in this study were outpatients at RSI Sultan Agung with a sample of 105 people, with the research instrument using a questionnaire. Data analysis uses univariate and bivariate analysis methods. The results showed that there was an influence of patient attitude variables (p=0.001, r=0.622), brand image (p=0.001, r=0.812), perceived value (p=0.001, r=0.700), perceived quality (p=0.001, r=0.565) on interest in revisiting. The conclusion of this research is that the variables of patient attitude, brand image, perceived value and perceived quality influence the interest in revisiting outpatients at RSI Sultan Agung Banjarbaru. Keywords: Patient Attitude, Brand Image, Perceived Value, Perceived Quality, Intention to Revisit